High-strength anti-static carrier tape base paper and preparation process thereof
By introducing TEMPO nano -oxidized nano -fiber and carbonized carbonized nanotubes in the carrier belt, the problem of insufficient band original paper, weakly combined with layers, and non -electrostatic electricity The effect is suitable for high -precision packaging and transportation of electronic components.
Patent Information
- Application Number
- CN202411821877.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing carrier tape base paper is insufficient in strength, weak interlayer bonding, and no static electricity protection, making it difficult to meet the high precision and high performance requirements for electronic components packaging and transportation.
By introducing functional adhesive components, TEMPO oxidize nano -fiber and carbon -based carbon nanotubes, improve the intensity and inter -layer binding force of the raw paper, and has anti -static function.
The raw paper with high intensity, anti -static and high -rise binding force is implemented, which is suitable for electronic component carrier paper for new energy vehicles, flexible display equipment and biomedical devices.
Smart Images

Figure CN119372959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special papermaking and carrier paper, and particularly relates to a high-strength antistatic carrier base paper and a preparation process thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Carrier paper is a special paper material used for packaging electronic components. It can not only protect the electronic components during transportation, but also be used for indexing and positioning. With the miniaturization of integrated circuits, electronic components are moving towards miniaturization. The sizes of transistors, resistors, capacitors, etc. are getting smaller and smaller. The demand for carrier paper is becoming more urgent and demanding, and the overall requirements are miniaturization, high precision, high performance, and functionality. Carrier paper is divided into embossed carrier paper and stamped carrier paper according to the forming process. Among them, embossed carrier paper is formed by producing a local cavity through mold imprinting, and stamped carrier paper is formed by punching to form a semi-penetrating cavity. Generally, paper carriers are favored by the market due to the advantages of no chamfering in punching, easy elimination of static electricity, good resilience, and low cost.
[0004] The carrier paper used for packaging and transportation of electronic components generally requires small thickness fluctuation, no delamination, high strength, water and moisture resistance to avoid problems such as easy breakage of the carrier tape and easy shedding of fiber dust. For example, the thickness should be 0.35-1.2mm, and the internal bonding strength should be >150J / m 2 , smoothness>500s. Patent CN1629401A adds rosin filler in the middle layer to make a carrier paper with small thickness change and no impact on operating efficiency; Patent CN1593910A avoids paper layer damage when carrier paper is peeled off by introducing styrene-acrylic resin; Patent CN118420944A improves interlayer bonding and antistatic effect by introducing nanocellulose and multi-walled carbon nanotubes. However, due to the limited bonding strength of cellulose fiber into paper, there are often problems such as weak interlayer bonding, low antistatic control accuracy, and difficulty in introducing functional components. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength antistatic carrier base paper and its preparation process, by introducing functional adhesive components TEMPO oxidized nanocellulose and carboxylated carbon nanotubes to solve the problems of insufficient strength, weak interlayer bonding and no antistatic of existing carrier base paper.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a process for preparing a high-strength antistatic carrier base paper, comprising:
[0008] Preparation of TEMPO-oxidized nanocellulose suspension;
[0009] The chemical coniferous wood pulp and the mechanical coniferous wood pulp are pre-treated by beating, mixed, and then dispersed to obtain a mixed pulp;
[0010] Adding TEMPO-oxidized nanocellulose suspension and carboxylated carbon nanotubes to the mixed slurry, and dispersing again to obtain a mixed suspension slurry system;
[0011] The mixed suspension slurry system is made into base paper to obtain base paper.
[0012] In some embodiments, the method for preparing the TEMPO-oxidized nanocellulose suspension comprises:
[0013] The cellulose fibers are diluted with water to prepare a suspension, TEMPO, sodium bromide and sodium hypochlorite are added, and the pH is adjusted to 10.4-10.6 before reacting. After the reaction is completed, the fibers are washed to neutrality, and high-pressure homogenized to obtain a TEMPO-oxidized nanocellulose suspension.
[0014] In some embodiments, the usage ratio of TEMPO, sodium bromide and sodium hypochlorite is 0.010-0.015 g: 0.05-0.10 g: 4-5 mmol.
[0015] The fibers in coniferous pulp are long and thin, with fewer impurities, and the carrier paper prepared from them has good flexibility, high folding resistance, and excellent tensile strength. Chemical pulp is pulp prepared by chemical methods, with ideal fiber length and excellent papermaking performance; mechanical pulp is prepared by mechanical action, with high yield, low pollution, and relatively long fiber length, but the papermaking strength is not high. The combination of the two can better achieve a balance in the performance of carrier paper. Therefore, in some embodiments, the absolute dry mass ratio of the chemical coniferous pulp to the mechanical coniferous pulp is 4-5:6-7.
[0016] It should be noted that the present invention does not specifically limit the specific production process and raw materials of chemical softwood pulp and mechanical softwood pulp. It is only necessary to control the beating degree of the two to meet the process requirements of the present invention. Therefore, in some embodiments, the beating degree of the chemical softwood pulp after beating pretreatment is 45-50°SR;
[0017] In some embodiments, the beating degree of the mechanical softwood pulp after pulping pretreatment is 42 to 50° SR;
[0018] In some embodiments, the rotation speed of the primary deflaking is 22000-28000 rpm.
[0019] In some embodiments, the ratio of the TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes, and mixed slurry insulation is 10-15 mL: 0.2-0.3 g: 1.5-1.7 g;
[0020] In some embodiments, the re-deflation speed is 10000-15000 rpm.
[0021] In some embodiments, the method for preparing the base paper comprises: adding water, homogenizing, dehydrating, pressing, and vacuum-assisted drying the mixed suspension slurry system to obtain the base paper.
[0022] In some embodiments, the amount of water added is 1.5 to 2.0 L, and the number of homogenization times is 8 to 10 times.
[0023] In some embodiments, the dehydration time is 10 to 15 seconds.
[0024] In some embodiments, the pressing requires absorbent felt pads on the upper and lower sides, the pressing pressure is 8.5 to 10.5 MPa, and the time is 10 to 15 minutes;
[0025] In some embodiments, the drying temperature is 99-105° C., the drying time is 11-14 min, and the vacuum degree is 3-5 MPa.
[0026] The second aspect of the present invention provides a high-strength antistatic carrier base paper prepared by the above method.
[0027] The third aspect of the present invention provides the use of the above-mentioned high-strength antistatic carrier paper in the preparation of electronic components.
[0028] Beneficial effects of the present invention
[0029] The present invention uses TEMPO-oxidized nanocellulose and carboxylated carbon nanotubes as functional components. The reagents and raw materials used are all conventional medicines, which have the advantages of being easily available and cost-controlled, and lay a formula foundation for the industrialization of carrier paper. Introducing TEMPO-oxidized nanocellulose and carboxylated carbon nanotubes into paper is expected to prepare high-strength antistatic carrier paper, solving the problems of insufficient strength, weak interlayer bonding, and no antistatic of traditional carrier paper, and can be used for the preparation of high-precision electronic component carrier paper for new energy vehicles, flexible display equipment, and biomedical devices.
[0030] Secondly, unlike the existing carrier paper, the preparation process of the present application introduces carboxylated carbon nanotubes as conductive functional components to adjust the conductive properties and anti-static function of the carrier paper, which can avoid the damage of static electricity caused by friction of paper materials to electronic components and reduce transportation loss rate.
[0031] Furthermore, the carboxylated carbon nanotubes have abundant carboxyl groups, which can form hydrogen bonds with fibers with high beating degree after dispersion, thus ensuring their uniform dispersion and retention rate, avoiding the loss of functional fillers and the burden of handling white water in engineering production.
[0032] Furthermore, in order to adjust the strength of the carrier paper and the interlayer bonding strength and avoid the problem of paper shedding and powdering, the present application preferably uses TEMPO oxidized nanocellulose as the reinforcing component. By regulating the viscosity, density and fluid properties of the slurry, the papermaking uniformity and the strength of the paper interface are improved. This is mainly because TEMPO oxidized nanocellulose has excellent drying self-filming properties.
[0033] Furthermore, considering that the carrier paper in practical applications requires high precision and multiple pins, the TEMPO-oxidized nanocellulose of the present invention is integrally formed into paper, which has higher plasticity, is conducive to continuous punching and improving manufacturing efficiency and automation level. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute improper limitations on the present invention.
[0035] Figure 1 The figure is a schematic diagram of the preparation process of an embodiment of the present invention. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0038] In the following examples, chemical softwood pulp, mechanical softwood pulp and various reagents are all commercially available products.
[0039] Example 1
[0040] Step 1, dilute cellulose fibers with water and stir them into a suspension, add TEMPO, sodium bromide and sodium hypochlorite, adjust the pH with potassium hydroxide solution and react for 2 hours; then wash with deionized water to neutrality, and homogenize under high pressure to obtain TEMPO-oxidized nanocellulose suspension A.
[0041] Among them, the concentration of the diluted cellulose fiber suspension is 8 mg / mL, and the ratio of the added TEMPO, sodium bromide and sodium hypochlorite is 0.01 g: 0.05 g: 4 mmol; the concentration of the potassium hydroxide solution is not limited, and the pH of the mixed system is adjusted to 10.4; the number of washing times is not limited, and the suspension concentration is washed to 6.8; the high-pressure homogenization pressure is 60 MPa, and the number of times is 15 times.
[0042] Step 2: pre-pulping the chemical softwood pulp and the mechanical softwood pulp respectively to improve the degree of fibrillation and beating, and then prepare a mixed suspension in a certain proportion and disperse to obtain a mixed pulp B;
[0043] Among them, the chemical softwood pulp was pretreated to 45°SR, and the mechanical softwood pulp was pretreated to 46°SR; after the pretreatment, the absolute dry mass ratio of the chemical softwood pulp to the mechanical softwood pulp was 4:6, and the deflaking speed was 22000rpm.
[0044] Step 3: adding TEMPO-oxidized nanocellulose suspension A and carboxylated carbon nanotubes (commercially available products) to the mixed slurry B, and dispersing again to obtain a mixed suspension slurry system C;
[0045] The ratio of the added TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and the insulating amount of the mixed slurry B was 10 mL: 0.2 g: 1.5 g, and the re-disintegration rotation number was 10000 rpm.
[0046] Step 4: The mixed suspension slurry system C is subjected to water addition, homogenization, dehydration in a paper sheet former, pressing in a flat vulcanizer, and vacuum-assisted drying to obtain a high-strength antistatic carrier base paper.
[0047] Among them, the amount of water added is 1.5L, the number of homogenization times is 8 times; the dehydration time is 10s, the flat vulcanizing press needs to be padded with absorbent felt on the top and bottom, the pressing pressure is 8.5MPa, and the time is 10min; the drying temperature is 99℃, the time is 11min, and the vacuum degree is 3MPa.
[0048] The basis weight of the carrier paper in this embodiment is 95 g / m 2 , the paper retention rate is 87%, and the interlayer bonding strength is 256J / m 2 The tensile strength is 17kN / mm, the surface strength is 3m / s, the moisture content is 5.5%, and the conductivity is 15S / cm. It has high strength, high bonding strength, and anti-static functions. In addition, the process is relatively stable, the engineering operability is strong, the comprehensive cost is controllable, and it has good application value.
[0049] Example 2
[0050] Step 1, dilute cellulose fibers with water and stir them into a suspension, add TEMPO, sodium bromide and sodium hypochlorite, adjust the pH with potassium hydroxide solution and react for 2 hours; then wash with deionized water to neutrality, and homogenize under high pressure to obtain TEMPO-oxidized nanocellulose suspension A.
[0051] Among them, the concentration of the diluted cellulose fiber suspension is 9 mg / mL, and the ratio of the added TEMPO, sodium bromide and sodium hypochlorite is 0.012 g: 0.06 g: 4.2 mmol; the concentration of the potassium hydroxide solution is not limited, and the pH of the mixed system is adjusted to 10.5; the number of washing times is not limited, and the suspension concentration is washed to 6.9; the high-pressure homogenization pressure is 63 MPa, and the number of times is 17 times.
[0052] Step 2: pre-pulping the chemical softwood pulp and the mechanical softwood pulp respectively to improve the degree of fibrillation and beating, and then prepare a mixed suspension in a certain proportion and disperse to obtain a mixed pulp B;
[0053] Among them, the chemical softwood pulp was pretreated to 46°SR, and the mechanical softwood pulp was pretreated to 43°SR; after pretreatment, the absolute dry mass ratio of chemical softwood pulp to mechanical softwood pulp was 4.5:6, and the debonding speed was 23000rpm.
[0054] Step 3: adding TEMPO-oxidized nanocellulose suspension A and carboxylated carbon nanotubes to the mixed slurry B, and dispersing again to obtain a mixed suspension slurry system C;
[0055] The ratio of the added TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and the insulating amount of the mixed slurry B was 11 mL: 0.25 g: 1.6 g, and the re-disintegration rotation number was 11000 rpm.
[0056] Step 4: The mixed suspension slurry system C is subjected to water addition, homogenization, dehydration in a paper sheet former, pressing in a flat vulcanizer, and vacuum-assisted drying to obtain a high-strength antistatic carrier base paper.
[0057] Among them, the amount of water added is 1.6L, the number of homogenization times is 9 times; the dehydration time is 11s, the flat vulcanizing press needs to use absorbent felt pads on the top and bottom, the pressing pressure is 9.0MPa, and the time is 11min; the drying temperature is 100℃, the time is 12min, and the vacuum degree is 4MPa.
[0058] The basis weight of the carrier paper in this embodiment is 95 g / m 2 , the paper retention rate is 88%, and the interlayer bonding strength is 241J / m 2The tensile strength is 16kN / mm, the surface strength is 4m / s, the moisture content is 5.8%, and the conductivity is 12S / cm. It has high strength, high bonding strength, and anti-static functions. In addition, the process is relatively stable, the engineering operability is strong, the comprehensive cost is controllable, and it has good application value.
[0059] Example 3
[0060] Step 1, dilute cellulose fibers with water and stir them into a suspension, add TEMPO, sodium bromide and sodium hypochlorite, adjust the pH with potassium hydroxide solution and react for 2 hours; then wash with deionized water to neutrality, and homogenize under high pressure to obtain TEMPO-oxidized nanocellulose suspension A.
[0061] The concentration of the diluted cellulose fiber suspension is 10 mg / mL, and the ratio of TEMPO, sodium bromide, and sodium hypochlorite added is 0.013 g: 0.08 g: 5 mmol; the concentration of the potassium hydroxide solution is not limited, and the pH of the mixed system is adjusted to 10.5;
[0062] There is no limit to the number of washing times, and the suspension concentration is 7.0; the high-pressure homogenization pressure is 72Mpa, and the number of times is 18 times.
[0063] Step 2: pre-pulping the chemical softwood pulp and the mechanical softwood pulp respectively to improve the degree of fibrillation and beating, and then prepare a mixed suspension in a certain proportion and disperse to obtain a mixed pulp B;
[0064] Among them, the chemical softwood pulp was pretreated to 48°SR, and the mechanical softwood pulp was pretreated to 50°SR; after pretreatment, the absolute dry mass ratio of chemical softwood pulp to mechanical softwood pulp was 4.8:6.2, and the debonding speed was 27000rpm.
[0065] Step 3: adding TEMPO-oxidized nanocellulose suspension A and carboxylated carbon nanotubes to the mixed slurry B, and dispersing again to obtain a mixed suspension slurry system C;
[0066] The ratio of the added TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and the insulating amount of the mixed slurry B was 14 mL: 0.28 g: 1.65 g, and the re-disintegration rotation number was 13000 rpm.
[0067] Step 4: The mixed suspension slurry system C is subjected to water addition, homogenization, dehydration in a paper sheet former, pressing in a flat vulcanizer, and vacuum-assisted drying to obtain a high-strength antistatic carrier base paper.
[0068] Among them, the amount of water added is 1.9L, the number of homogenization times is 9 times; the dehydration time is 14s, the flat vulcanizing press needs to be padded with absorbent felt on the top and bottom, the pressing pressure is 10MPa, and the time is 13min; the drying temperature is 102℃, the time is 13min, and the vacuum degree is 5MPa.
[0069] The basis weight of the carrier paper in this embodiment is 96 g / m 2 , the paper retention rate is 85%, and the interlayer bonding strength is 268J / m 2 The tensile strength is 17kN / mm, the surface strength is 3m / s, the moisture content is 3.7%, and the conductivity is 18S / cm. It has high strength, high bonding strength, and anti-static functions. In addition, the process is relatively stable, the engineering operability is strong, the comprehensive cost is controllable, and it has good application value.
[0070] Example 4
[0071] Step 1, dilute cellulose fibers with water and stir them into a suspension, add TEMPO, sodium bromide and sodium hypochlorite, adjust the pH with potassium hydroxide solution and react for 2 hours; then wash with deionized water to neutrality, and homogenize under high pressure to obtain TEMPO-oxidized nanocellulose suspension A.
[0072] The concentration of the diluted cellulose fiber suspension is 12 mg / mL, and the ratio of TEMPO, sodium bromide, and sodium hypochlorite added is 0.015 g: 0.10 g: 5 mmol; the concentration of the potassium hydroxide solution is not limited, and the pH of the mixed system is adjusted to 10.6;
[0073] There is no limit to the number of washing times, and the concentration of the suspension is 7.2; the high-pressure homogenization pressure is 80Mpa, and the number of times is 20 times.
[0074] Step 2: pre-pulping the chemical softwood pulp and the mechanical softwood pulp respectively to improve the degree of fibrillation and beating, and then prepare a mixed suspension in a certain proportion and disperse to obtain a mixed pulp B;
[0075] Among them, chemical softwood pulp was pretreated to 50°SR, and mechanical softwood pulp was pretreated to 50°SR; after pretreatment, the absolute dry mass ratio of chemical softwood pulp to mechanical softwood pulp was 5:7, and the deflaking speed was 28000rpm.
[0076] Step 3: adding TEMPO-oxidized nanocellulose suspension A and carboxylated carbon nanotubes to the mixed slurry B, and dispersing again to obtain a mixed suspension slurry system C;
[0077] The ratio of the added TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and the insulating amount of the mixed slurry B was 15 mL: 0.3 g: 1.7 g, and the re-disintegration rotation number was 15000 rpm.
[0078] Step 4: The mixed suspension slurry system C is subjected to water addition, homogenization, dehydration in a paper sheet former, pressing in a flat vulcanizer, and vacuum-assisted drying to obtain a high-strength antistatic carrier base paper.
[0079] Among them, the amount of water added is 2.0L, the number of homogenization times is 10 times; the dehydration time is 15s, the flat vulcanizing press needs to be padded with absorbent felt on the top and bottom, the pressing pressure is 10.5MPa, and the time is 15min; the drying temperature is 105℃, the time is 14min, and the vacuum degree is 5MPa.
[0080] The basis weight of the carrier paper in this embodiment is 96 g / m 2 , the paper retention rate is 90%, and the interlayer bonding strength is 248J / m 2 The tensile strength is 18kN / mm, the surface strength is 3m / s, the moisture content is 6.2%, and the conductivity is 17S / cm. It has the functions of high strength, high bonding strength, and anti-static. In addition, the process is relatively stable, the engineering operability is strong, the comprehensive cost is controllable, and it has good application value.
[0081] Example 5
[0082] Step 1, dilute cellulose fibers with water and stir them into a suspension, add TEMPO, sodium bromide and sodium hypochlorite, adjust the pH with potassium hydroxide solution and react for 2 hours; then wash with deionized water to neutrality, and homogenize under high pressure to obtain TEMPO-oxidized nanocellulose suspension A.
[0083] The concentration of the diluted cellulose fiber suspension is 10 mg / mL, and the ratio of TEMPO, sodium bromide, and sodium hypochlorite added is 0.014 g: 0.9 g: 4 mmol; the concentration of the potassium hydroxide solution is not limited, and the pH of the mixed system is adjusted to 10.4;
[0084] There is no limit to the number of washing times, and the concentration of the suspension is 6.8; the high-pressure homogenization pressure is 61Mpa, and the number of times is 15 times.
[0085] Step 2: pre-pulping the chemical softwood pulp and the mechanical softwood pulp respectively to improve the degree of fibrillation and beating, and then prepare a mixed suspension in a certain proportion and disperse to obtain a mixed pulp B;
[0086] Among them, the chemical softwood pulp was pretreated to 50°SR, and the mechanical softwood pulp was pretreated to 48°SR; after pretreatment, the absolute dry mass ratio of the chemical softwood pulp to the mechanical softwood pulp was 4:7, and the debonding speed was 28000rpm.
[0087] Step 3: adding TEMPO-oxidized nanocellulose suspension A and carboxylated carbon nanotubes to the mixed slurry B, and dispersing again to obtain a mixed suspension slurry system C;
[0088] The ratio of the added TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and the insulating amount of the mixed slurry B was 15 mL: 0.2 g: 1.5 g, and the re-disintegration rotation number was 10000 rpm.
[0089] Step 4: The mixed suspension slurry system C is subjected to water addition, homogenization, dehydration in a paper sheet former, pressing in a flat vulcanizer, and vacuum-assisted drying to obtain a high-strength antistatic carrier base paper.
[0090] Among them, the amount of water added is 1.5L, the number of homogenization times is 10 times; the dehydration time is 10s, the flat vulcanizing press needs to be padded with absorbent felt on the top and bottom, the pressing pressure is 10.5MPa, and the time is 15min; the drying temperature is 105℃, the time is 11min, and the vacuum degree is 3MPa.
[0091] The basis weight of the carrier paper in this embodiment is 97 g / m 2 , the paper retention rate is 88%, and the interlayer bonding strength is 258J / m 2 The tensile strength is 19kN / mm, the surface strength is 2m / s, the moisture content is 4.6%, and the conductivity is 20S / cm. It has high strength, high bonding strength, and anti-static functions. In addition, the process is relatively stable, the engineering operability is strong, the comprehensive cost is controllable, and it has good application value.
[0092] Comparative Example 1
[0093] The difference from Example 1 is that in step 3, cationic starch is used to replace mixed slurry B, and the absolute dry masses of the two are the same.
[0094] The basis weight of the carrier paper in this comparative example is 95 g / m 2 , the paper retention rate is 78%, and the interlayer bonding strength is 167J / m 2 , tensile strength is 12kN / mm, surface strength is 1m / s, moisture content is 5.7%, and conductivity is 8S / cm.
[0095] Comparative Example 2
[0096] The difference from Example 1 is that in step 2, only chemical softwood pulp is used, and the total amount of pulp remains unchanged.
[0097] The basis weight of the carrier paper in this comparative example is 95 g / m 2 , the paper retention rate is 86%, and the interlayer bonding strength is 162J / m 2 , tensile strength is 13kN / mm, surface strength is 3m / s, moisture content is 5.4%, and conductivity is 14S / cm.
[0098] Comparative Example 3
[0099] The difference from Example 1 is that in step 2, only mechanical softwood pulp is used and the total amount of pulp remains unchanged.
[0100] The basis weight of the carrier paper in this comparative example is 95 g / m 2 , the paper retention rate is 77%, and the interlayer bonding strength is 230J / m 2 , tensile strength is 14kN / mm, surface strength is 2m / s, moisture content is 5.7%, and conductivity is 16S / cm.
[0101] From the comparison between Example 1 and Comparative Example 1, it can be seen that, compared with cationic starch, the mixed slurry B can obtain better interlayer bonding strength of paper, and the electrical conductivity and paper strength are also enhanced.
[0102] From the comparison between Example 1 and Comparative Examples 2 and 3, it can be seen that, compared with using only mechanical softwood pulp or chemical softwood pulp, the combination of the two can better improve the interlayer bonding strength and tensile strength of paper.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a high-strength antistatic carrier base paper, characterized in that: include: Preparation of TEMPO-oxidized nanocellulose suspension; The chemical coniferous wood pulp and the mechanical coniferous wood pulp are pre-treated by beating, mixed, and then dispersed to obtain a mixed pulp; Adding TEMPO-oxidized nanocellulose suspension and carboxylated carbon nanotubes to the mixed slurry, and dispersing again to obtain a mixed suspension slurry system; The mixed suspension slurry system is made into base paper to obtain base paper.
2. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The preparation method of the TEMPO-oxidized nanocellulose suspension comprises: The cellulose fibers are diluted with water to prepare a suspension, TEMPO, sodium bromide and sodium hypochlorite are added, and the pH is adjusted to 10.4-10.6 before reacting. After the reaction is completed, the fibers are washed to neutrality, and high-pressure homogenized to obtain a TEMPO-oxidized nanocellulose suspension.
3. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The usage ratio of TEMPO, sodium bromide and sodium hypochlorite is 0.010-0.015 g: 0.05-0.10 g: 4-5 mmol.
4. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The absolute dry mass ratio of the chemical softwood pulp to the mechanical softwood pulp is 4-5:6-7.
5. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The beating degree of chemical softwood pulp after pulping pretreatment is 45-50°SR; Or, the beating degree of the mechanical softwood pulp after beating pretreatment is 42-50°SR; Alternatively, the rotation speed of the primary decomposition is 22000-28000 rpm.
6. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The ratio of the TEMPO-oxidized nanocellulose suspension, carboxylated carbon nanotubes and mixed slurry insulation is 10-15 mL: 0.2-0.3 g: 1.5-1.7 g; Or, the speed is reduced to 10000-15000 rpm again.
7. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The preparation method of the base paper comprises: adding water to the mixed suspension slurry system, homogenizing, dehydrating, pressing, and vacuum-assisted drying to obtain the base paper.
8. The process for preparing the high-strength antistatic carrier base paper according to claim 1, characterized in that: The amount of water added is 1.5-2.0L, and the number of homogenization times is 8-10 times; Or, the dehydration time is 10 to 15 seconds; Or, the pressing needs to be padded with absorbent felt above and below, the pressing pressure is 8.5-10.5MPa, and the pressing time is 10-15min; Alternatively, the drying temperature is 99-105°C, the drying time is 11-14 minutes, and the vacuum degree is 3-5 MPa.
9. The high-strength antistatic carrier base paper prepared by the method according to any one of claims 1 to 8.
10. Use of the high-strength antistatic carrier paper according to claim 9 in the preparation of electronic components.
Citation Information
Patent Citations
Carrier band material and carrier band
CN1593910A
Carrier tape base paper and carrier tape
CN1629401A
Base paper of thin type packaging paper and preparation method thereof
CN107558295A
Anti-static hydroxyethyl fiber membrane for carrier tape paper and preparation method of hydroxyethyl fiber membrane
CN118420944A
Process for manufacturing original paper for paper carrier tape for sheet-like electronic element
CN1876957A
Cited By
Environment-friendly high-barrier packaging paper and preparation method thereof
CN121087844A